Membrane Computing 12th International Conference, CMC 2011, Fontainebleau, France, August 23-26, 2011, Revised Selected Papers - Gheorghe, Marian; Paun, Gheorghe; Rozenberg, Grzegorz; Salomaa, Arto; Verlan, Sergey (Theoretical Computer Science and General Issues,, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 12th International Conference on Membrane Computing, CMC 2011, held in Fontainebleau, France, in August 2011. The 19 revised selected papers presented were carefully reviewed and selected from 27 papers and 5 posters presented at the conference. The book also contains full papers or extended abstracts of the 5 invited presentations. The papers address all the main directions of research in membrane computing, ranging from theoretical topics in the mathematics and computer science to application issues.